2017
DOI: 10.3892/mmr.2017.6265
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor 1 receptor-mediated cell survival in hypoxia depends on the promotion of autophagy via suppression of the PI3K/Akt/mTOR signaling pathway

Abstract: Hypoxia is widely accepted as a fundamental biological phenomenon, which is strongly associated with tissue damage and cell viability under stress conditions. Insulin-like growth factor-1 (IGF-1) is known to protect tissues from multiple types of damage, and protect cells from apoptosis. Hypoxia is a regulatory factor of the IGF system, however the role of the IGF-1 receptor (IGF-1R) in hypoxia-induced apoptosis remains unclear. The present study investigated the potential mechanisms associated with IGF-1R-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 45 publications
(54 reference statements)
0
28
0
Order By: Relevance
“…Research on the correlation of PI3K/Akt/mTOR signaling pathway with malignant tumor has become the focus in recent years (13). The PI3K/Akt/mTOR signaling pathway not only plays a vital role in the growth and proliferation of normal cells, but is also closely related to the growth of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the correlation of PI3K/Akt/mTOR signaling pathway with malignant tumor has become the focus in recent years (13). The PI3K/Akt/mTOR signaling pathway not only plays a vital role in the growth and proliferation of normal cells, but is also closely related to the growth of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is regarded as a cellular self-digestion process in response to a wide range of deleterious stimuli, through which cytoplasmic materials or organelles integrate into lysosomes for further degradation (47). Previous studies have reported that, autophagy serves a crucial role in the development, differentiation, survival and homeostasis of cells (48)(49)(50)(51). During organ I/R injury, autophagy may help cells respond to injury.…”
Section: Discussionmentioning
confidence: 99%
“…IGF1R phosphorylation induces the binding of IRS1 to IGF1R, which allows IRS1 to stimulate the PI3K pathway [53]. Further, IGF1R-mediated cell survival under stress conditions leads to enhanced activation of autophagy by the suppression of the PI3K-Akt-mTOR signaling pathway [54]. In Caenorhabditis elegans, genes of autophagy are important for life-span extension, in which autophagy is reported to have an influence on controlling the cell size converged by the growth modulator signaling pathways, the effects being mediated by insulin/IGF-1 or TGF-β signaling [55].…”
Section: Insulin-like Growth Factor-1 (Igf-1) Pathwaymentioning
confidence: 99%